Os sentidos da formação em Pedagogia da Terra: o caso das militantes do MST no estado de São Paulo - Rezende, Janaína Ribeiro de (Universidade Federal de São Carlos, 2010)
This research aims to analyze the meanings attributed to formation and knowledge usesacquired through the Land Pedagogy, by professionals who have worked with the MST(landless movement) in Sao Paulo State. For that, it was necessary to diagnose how manypeople graduated in this course, who fits in this working context, as well as gathering someinformation about their lives in order to identify their social origins, schooling, professionalcourse, participation conditions in MST, information about the Pedagogy Course they did,performance after graduation and their expectations for the future. To reach this study, wehave researched through literature and documents and performed semi-structured andstructured interviews with participants. For the analysis, we used data triangulation andconsensual validation. We have found eleven women who graduated in Education for RuralCommunities University Course Program and who have worked in Sao Paulo. Although therewere common points among them, for all come from poor backgrounds, there were alsodiverse life stories. Many of them migrated several times searching for better livingconditions and were employed in unskilled jobs which required no technical qualifications.The commitment with the struggle for land and Land Education is the common elementpresent in all stories, but the motivations which have led the participants to MST are quitedifferent. They have found through their social movement militancy a way to build referencesof life and sociability. The participants attended the Land Pedagogy course at Uijui, Unemat,Iterra/UERGS and Unioeste and all interviews positively accessed the education level offeredin it, in both political and educational aspects. Some of these professionals work in theMetropolitan Sao Paulo region, Promissão, Iaras Pontal and at Escola Nacional FlorestanFernandes. Among the others, two of them work outside São Paulo State, one of them inParaíba State e the other one in Mozambique, all of them developing activities for the MST.Among the participants, only one of them gave up militancy recently, although she hascontributed to the educational department over almost ten years. The other participants stillcontribute with the regional, state or national educational department. They develop a varietyof functions, taking more attention to the formal MST courses which are assumed by most ofthem. In Sao Paulo, none of them took the school teaching task because of the difficulties ofparticipation in these institutions and their personal political activity priority demanded by theMST in the state. Concerning the outlook for the future, all of them had an optimistic forecastseeking for projects linking all aspects of their personal lives, as women, mothers, rural settledand militants. As a result of this study, the data analysis identified that the meanings attributedto graduation are: increased schooling, qualified studies, pedagogical and political education,militancy appreciation, performance qualification and an established relation betweenformation or studies and performance or practice. Summarizing, we conclude that the usesand meanings attributed to Land Pedagogy graduation by our participants militants at MSTrefer to the maintenance of their contribution to this social movement. Therefore, we believethat the intention of the MST when leading them for the course was promoting the training ofstaff.
Keywords: Educação rural; Educação do campo; Pedagogia da terra; Educação - movimentos sociais; Education for rural communities; Land pedagogy; Social movements and education; CIENCIAS HUMANAS::EDUCACAO